2020
DOI: 10.1107/s2059798320009389
|View full text |Cite
|
Sign up to set email alerts
|

Structural alphabets for conformational analysis of nucleic acids available at dnatco.datmos.org

Abstract: A detailed description of the dnatco.datmos.org web server implementing the universal structural alphabet of nucleic acids is presented. It is capable of processing any mmCIF- or PDB-formatted files containing DNA or RNA molecules; these can either be uploaded by the user or supplied as the wwPDB or PDB-REDO structural database access code. The web server performs an assignment of the nucleic acid conformations and presents the results for the intuitive annotation, validation, modeling and refinement of nuclei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 40 publications
(33 reference statements)
0
12
0
Order By: Relevance
“…We do not discuss quantitative values that depend on the method used and consider the superposition areas qualitatively, i.e., small superposition (less than 1 Å 2 , frequently negligible ring overlap) or substantial overlap (more than 2 Å 2 ). The assignment of NtCs to optimized dDMPs and cdDMPs uses DNATCO software [28].…”
Section: Methodsmentioning
confidence: 99%
“…We do not discuss quantitative values that depend on the method used and consider the superposition areas qualitatively, i.e., small superposition (less than 1 Å 2 , frequently negligible ring overlap) or substantial overlap (more than 2 Å 2 ). The assignment of NtCs to optimized dDMPs and cdDMPs uses DNATCO software [28].…”
Section: Methodsmentioning
confidence: 99%
“…The homology model of the FOXO4/IRE complex was based on the available crystal structure 3l2c, extending the 3l2c template DNA sequence “–CTA­TG­TAA­AC­AAC–” to the IRE “GAC­TA­TC­AA­AA­CA­ACGC” sequence. The necessary nucleotide substitutions as well as residues missing at the 5′ and 3′ termini were modeled using the MMB program. , The backbone conformation of the newly built termini was set to the canonical B form DNA using dinucleotide conformation class (NtC) BB00. , The geometry of the initial model was further equilibrated during a 200 ns molecular dynamics simulation in GROMACS 2021.4 using the ff14SB force field for FOXO4 and the tumuc1 force field for DNA. The model was placed in a rectangular box with the 10 Å shortest distance from the walls.…”
Section: Experimental Sectionmentioning
confidence: 99%
“…All this information provides a goldmine for comparative studies on these factors, enabling trends in structure (and in other features such as DNA hydration) to be statistically assessed for large groups of structures (see, for example, refs. ( 101 , 102 , 103 , 104 )). Such data-mining studies have revealed for example that in duplex DNA sequences, the d(TA) step is the most flexible in terms of base step morphology parameters such as roll and tilt and thus can contribute to DNA helix bending ( 21 , 26 , 27 , 28 , 29 , 30 , 31 ).…”
Section: The Importance Of the Pdb And Ndb For Studies On Dna Structure Flexibility And Functionmentioning
confidence: 99%